Islamic Foundations of Sustainable Employee Behavior: Evidence From The Noble Quranic Verses And Hadith - Souad Mahdi; Nurazmallail Marni (Universiti Sains Islam Malaysia, 2024)
Ulum Islamiyyah: Malaysian Journal of Islamic Sciences Volume 36 Issue 1 Page (8-22)